High-capacitance Ti3C2Tx MXene obtained by etching submicron Ti3AlC2 grains grown in molten salt. Issue 58 (5th July 2018) - Cui, Cong; Hu, Minmin; Zhang, Chao; Cheng, Renfei; Yang, Jinxing; Wang, Xiaohui
Abstract : The capacitance of small-sized Ti3 C2 T x MXene particulates is more than twice that of the large ones. Abstract : Submicron Ti3 AlC2 grains are grown in molten salt. Etching the grains gives rise to small-sized Ti3 C2 T x MXene particulates with capacitance more than twice that of the large ones derived from conventional high-temperature synthesis. Detailed electrochemical, structural, and spectroscopic studies demonstrate that increased capacitance predominantly originates from a decrease in the lateral size of the small Ti3 C2 T x MXene particulates.